الشّيخ محمد شريف الله وجهوده الدعوية من خلال التفاسيره الثلاثة: Muhammad Sharifulllah and his efforts in the field of Daʻwah in his three Tafāsīr (Al-Qamar, 2023)
Many scholars of the Indian subcontinent have spent their lives in the service of the religion of Islam and filled the Indian continent with their knowledge in particular and the world in general. Among them is the preacher Sheikh Muhammad Sharif who had tremendous efforts in the field of Daʼwah. He spent his life in Daʼwah. The present article revolves around his preaching efforts in his three tafāsīr. It gives a brief account of his life in the introduction, and includes two sections and a conclusion. The first section deals with his Daʼwah efforts through his three commentaries of the Quan and his style in these tafāsīr, and the second one covers the means of Daʼwah adopted by him. Finally, the conclusion and findings of the research have been presented.
Keywords: Sharifullah; effort; daʻwah; Tafsīr